PENGARUH MODEL PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA MENGGUNAKAN APLIKASI WOLFRAM ALPHA - LUBIS, MHD. ILYAS; Israq Maharani; Fatmah Syarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of generative learning model to improve students' mathematical concept understanding ability using Wolfram Alpha application in class VIII MTs Riyadhus Sholihin Sunggal. The research method uses quasi-experimental with Pretest-Posttest design. After conducting research and data analysis, the results of the pretest t_count value were 4.797 and the results of the posttest value were 4.760 with the obtained 2.074. So the result > which means is rejected and is accepted. In other words, there is an effect of generative learning model on improving students' mathematical concept understanding ability using Wolfram Alpha application. Therefore, the Generative Learning Model can be used as an alternative to improve students' mathematical concept understanding ability Keywords: Generative learning, Mathematical Concept Understanding Ability, Wolfram Alpha